Yeast colonies: a model for studies of aging, environmental adaptation, and longevity - Váchová, Libuše; Cáp, Michal; Palková, Zdena (Oxidative medicine and cellular longevity, 2012)
When growing on solid surfaces, yeast, like other microorganisms, develops organized multicellular populations (colonies and biofilms) that are composed of differentiated cells with specialized functions. Life within these populations is a prevalent form of microbial existence in natural settings that provides the cells with capabilities to effectively defend against environmental attacks as well as efficiently adapt and survive long periods of starvation and other stresses. Under such circumstances, the fate of an individual yeast cell is subordinated to the profit of the whole population. In the past decade, yeast colonies, with their complicated structure and high complexity that are also developed under laboratory conditions, have become an excellent model for studies of various basic cellular processes such as cell interaction, signaling, and differentiation. In this paper, we summarize current knowledge on the processes related to chronological aging, adaptation, and longevity of a colony cell population and of its differentiated cell constituents. These processes contribute to the colony ability to survive long periods of starvation and mostly differ from the survival strategies of individual yeast cells.
Keywords: životní prostředí; Longevity; kvasinky; Colony Count, Microbial; zvířata; Adaptation, Physiological; Animals; lidé; časové faktory; dlouhověkost; Environment; Time Factors; fyziologická adaptace; počet mikrobiálních kolonií; Humans; Yeasts; Models, Biological; biologické modely